Maternal Obesity Affects the Glucose-Insulin Axis During the First Trimester of Human Pregnancy - Bandres-Meriz, Julia; Dieberger, Anna M.; Hoch, Denise; Pöchlauer, Caroline; Bachbauer, Martina; Glasner, Andreas; Niedrist, Tobias; van Poppel, Mireille N. M.; Desoye, Gernot (Frontiers in Endocrinology, 2020)
Background and objective: The maternal glucose-insulin axis is central for metabolic adaptations required for a healthy pregnancy. Metabolic changes in obese mothers in early pregnancy have been scantly described. Here we characterized the glucose-insulin axis in the first trimester of human pregnancy and assessed the effect of maternal obesity and fat mass. Methods: Maternal blood samples (n=323) were collected during voluntary pregnancy termination (gestational age 4+0 - 11+6 weeks) after overnight fasting. Smokers (n=198) were identified by self-report and serum cotinine levels (ELISA). Maternal BMI (kg/m2) and serum leptin (ELISA) were used as proxy measures of obesity and maternal fat mass, respectively. ISHOMA insulin sensitivity index was calculated from glucose and C-peptide (ELISA) serum concentrations. Results: Glucose and C-peptide levels decreased (P < 0.001) between weeks 4-6 and 7-9, paralleled by an increase (P < 0.001) in insulin sensitivity. Glucose levels were not significantly different between BMI or leptin categories. In contrast, compared to the normal-weight /low fat mass group, C-peptide was higher in the obese (OR 1.66, CI 1.42-1.93; P < 0.001) and high fat mass group (OR 1.25, CI 1.13-1.33; P <0.001) whereas ISHOMA was lower (OR 0.57, CI 0.48-0.68; P <0.001 and OR 0.67, CI 0.60-0.76; P <0.001) respectively. Conclusions: Glucose, C-peptide and insulin sensitivity dynamically change in the first trimester of human pregnancy. Maternal obesity is associated with higher C-peptide and lower insulin sensitivity at all stages, while glucose is unaltered. These findings have implications for the timing of early gestational diabetes mellitus risk screening.